Canada during the First World War: Conducting a Universal Registration of Labor Resources (based on the Canadian Press) - E. S. Simonenko (Научный диалог)
The article is devoted to the study of the Canadian government’s policy in the field of labor mobilization of the population during the First World War. The author limits the presentation of events to 1916, when the concept of compulsory labor service was developed and implemented. The article proved that the universal registration of labor in Canada was the first step towards introducing compulsory labor service and, as a result, became the basis for abandoning the voluntary system of recruitment into the army and the gradual transition to compulsory military service (conscription). The projects of conducting a universal census of labor resources, developed by supporters and opponents of conscription, are being studied. The process of institutionalizing the labor mobilization of the Canadian population is described on the example of the creation and activities of two state bodies: the government Council for labor service and the parliamentary Committee for labor service. The features of the mechanism for the inventory of labor resources, including the structure of registration cards, the conditions for filling them in, as well as the circumstances of its implementation, are investigated. The results of the general census of labor are summarized, the protest movement among Canadian workers who for various reasons refused to participate in the universal registration of labor resources is studied.